Distribution and Revenue Sharing of Natural Resources in Indonesia: Autonomous Region and Legal Pluralism Perspective - Putu Gede Arya Sumerta Yasa (Faculty of law Udayana University, 2021)
The distribution and revenue sharing of natural resources in Indonesia is considered a very important issue. The exploitation of natural resources of a particular region can be implemented by referring to the concept of regional autonomy. In practice, not all regional governments can take advantage of the natural resources situated in the region. The research aims to review and analyze the arrangement of revenue sharing and natural resources based on the principle of decentralization in the balance of national and regional finances in Indonesia and analyze the autonomous region in Indonesia from a legal pluralism perspective. This study is normative legal research using statutory, conceptual, and analytical approaches. The results suggested that the arrangement of the division of funds for revenue based on decentralization in Indonesia has not fully reflected the principle of proportionality, as it is perceived not providing just and proper share for some regions. In achieving public welfare and social justice at the lowest level of governance, the existence of customary villages in Bali may serve as a solution in addressing the issue of regional management on natural resources along with its potential benefits. Parallel to this concern, the customary village can also play an indirect role in achieving justice, equity, and harmony in the regions. Therefore, the synergy between the national and regional governments, including customary villages undoubtedly reflects legal pluralism.